Howard Goldblattâs translation practice and translation thoughts - Zuo, Yunchao; Ng, Chwee Fang; Md Rashid, Sabariah; Toh, Florence Haw Ching (Human Resource Management Academic Research Society, 2021)
With the cultural turn of translation studies, the subject status of translators has gradually been highlighted, and translator studies have become increasingly important. However, the current research on translators is mostly confined to certain aspects such as the translator’s translation thoughts, translation strategies or translation styles, which lacks comprehensive and detailed research. This article aims to study the translator Howard Goldblatt from the four aspects of his life experience, namely translation practice, translation motivation, translation thoughts and translation strategies, in an attempt to present a detailed and comprehensive translator. The results demonstrate that Howard Goldblatt’s translation is based on cross-cultural communication as the ultimate goal, comprehensively using translation strategies that combine domestication and foreignization to spread the Chinese culture. This study contributes to the diversification of research methods and the dissemination of Chinese culture.